Synthesis of dihydroquinoxalin-2(1H)-ones by tin powder-promoted di- and mono-allylation of quinoxalin-2(1H)-ones. Issue 20 (15th May 2020) - Deng, Zhoubin; Yang, Tianyu; Wang, Ke-Hu; Xue, Wenxuan; Huang, Danfeng; Li, Pengfei; Wang, Junjiao; Su, Yingpeng; Hu, Yulai
Abstract: An efficient method of tin powder-promoted di- and mono-allylation of quinoxalin-2(1 H )-ones has been developed, which provides a practical route for the synthesis of dihydroquinoxalin-2(1 H )-one derivatives in good yields. This protocol uses the combination of allylbromides and tin powder to replace the traditional allylstannanes to make the organotin-participated process less toxic, and has the advantages of readily available starting materials, mild reaction conditions, and a wide scope of substrates. Graphical abstract: Image 1 Highlights: 3, 4-Diallyl-3, 4-dihydroquinoxalin-2(1H)-ones and 3-allyl-3, 4-dihydroquinoxalin-2(1 H )-ones have been synthesized through tin-promoted allylation.